Integration of lean manufacturing and quality management system through structural equation modeling - Khalili, Amjad; Ismail, Md Yusof; Karim, A.N. Mustafizul (Inderscience Publishers, 2017)
Both the LM (Lean Manufacturing) and the QMS (Quality Management System) are clear initiatives with a goal of improving effectiveness and efficiencies. This review paper aims at exploring the impact of Lean Manufacturing tools (LM) on Quality Management system (QMS). Many organizations tackle Lean philosophy, ISO 9001standard individually. But this kind of attempt lacks focus on the synergy and the advantage from the potential collaboration. Few studies were conducted to explore the linkage between LM and QMS, and little is known about the interrelatedness between these constructs and whether they can coexist in the Manufacturing Industries or not. Though LM is generally proposed as a driver for QMS, a conceptual model is necessary to be developed in order to investigate the integration between LM and QMS.A conceptual model is proposed in this paper with a future direction of empirical investigation of the model using AMOS 22 Structural Equation Modeling to test the proposition of the study. The originality of this paper lies in observing and measuring the impact of 11 LM tools on the QMS implementation with eventual contribution to Operations Management by focusing on hard LM aspects and their interrelationships with QMS in one integrated model.